Energy security and geopolitics in the Arctic challenges and opportunities in the 21st century - Peimani, Hooman (World Scientific Pub., 2013)
This book sheds light on how global warming has caused the ongoing environmental disaster in the Arctic, namely its melting. This development, if left unabated, will have a major negative environmental impact, not only on the Arctic itself, but on the entire planet, including the worsening of global warming and rising sea levels.